2017
DOI: 10.15761/imm.1000275
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin-rich chrysanthemum flower extract suppresses baseline serum uric acid in Japanese subjects with mild hyperuricemia

Abstract: Background: Luteolin is a flavonoid found in various edible plants that exhibits diverse health benefits, including anti-inflammatory and anti-gout effects. However, there has been little clinical investigation of luteolin from the viewpoint of gout prevention. We conducted a clinical trial of supplementation with chrysanthemum flower extract rich in luteolin (LCE) to assess the effect on serum uric acid levels in Japanese men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…The single oral dosing study showed no significant changes in serum uric acid levels between the CFE and placebo groups (Figure 2). This result was consistent with our previous findings [15]. Serum uric acid after 12-week ingestion of CFE, which was set as the primary outcome, was significantly lower in the CFE group than in the placebo group (Table 2).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The single oral dosing study showed no significant changes in serum uric acid levels between the CFE and placebo groups (Figure 2). This result was consistent with our previous findings [15]. Serum uric acid after 12-week ingestion of CFE, which was set as the primary outcome, was significantly lower in the CFE group than in the placebo group (Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…Ltd. [15]. Collectively, these findings indicate that the consecutive ingestion of CFE decreases serum uric acid levels.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Many in vitro studies have been performed to investigate the XO inhibitory mechanism of phenolic acids and bioactive flavonoids, such as chrysin, kaempferol and quercetin [5,6,7]. Numerous in vivo studies on the anti-hyperuricemic activity of other plant extracts have also been conducted [5,8], but investigation on C. molifolium has not been well performed in a greater depth. Therefore, the present study is the first in vitro and in vivo investigation on the potential of C. morifolium flower sub-fractions in XO inhibition and the determination of its antihyperuricemic activity followed by XO mRNA gene expression study.…”
Section: Introductionmentioning
confidence: 99%